Regression Modeling and Process Analysis of Resistance Spot Welding on Dissimilar Steel Sheets - Ternane, F.; Benachour, M.; Sebaa, F.; Benachour, N. (Engineering, Technology & Applied Science Research, 2022)
The resistance spot welding process is used to weld dissimilar materials. Dissimilar joining is formed by two 2mm thick sheet metals of 304L austenitic stainless steel and galvanized steel. This study investigates the effects of welding parameters such as welding current, welding time, and welding force. The welding time and the welding force were, respectively, in the range of 10-13 cycles and 7-8bar, while the welding current was in the range of 10–16kA. Tensile tests were applied to determine the resistance parameters of dissimilar joining. The experimental results showed that increasing the welding current increased the tensile shear stress of the weld coupon. Regression analysis was carried out to determine the significance of the process parameters by using the coupled of the full factorial experimental design with statistical and graphical analysis of the results. Furthermore, analysis of variance was used to determine the optimal parameters and combinations to achieve the highest strength level.